Term papers: A chance or challenge for university students? - Sarair, Sarair; Trisnawati, Ika Kana; Nurfaizah, Nurfaizah (Englisia: Journal of Language, Education, and Humanities, 2024)
This study aims to investigate how university students perceive term papers as part of their course assignments. The study used the qualitative research method to collect the data. The data were obtained by means of semi-structured interview. A total of 20 students majoring in English Education participated in the study, selected using random sampling technique. The data were then analyzed by using thematic analysis. The findings revealed that the students viewed term papers as a chance to develop their knowledge as well as motivation and confidence. On the other hand, some also perceived that term paper assignments were challenging due to several factors, such as lack of learning resources, lack of cooperation, lack of ability to explain difficult topics, and lack of academic writing and critical thinking skills. This study suggests that lecturers foster student collaboration, offer personalized assistance, and provide explicit instructions on scientific writing in order to make term paper assignments easier and beneficial to all students in higher education.